PENGEMBANGAN SUMBER DAYA MANUSIA DALAM PENINGKATAN MUTU LULUSAN PADA LEMBAGA PENDIDIKAN ISLAM DI KABUPATEN - Andi Warisno (Ri'ayah: Jurnal Sosial dan Keagamaan, 2019)
The problem facing the madrasa today, is that there are still very fundamental internal problems, in all the education system, especially the management system and a low work ethic, the quality and quantity of inadequate Educators, ineffective curricula, and physical facilities and facilities that are still not enough. Because these factors make the madrasa receive less response from the community, so that its existence becomes marginalized from the world of education. Although many problems arise from the implementation of the Islamic education system in the madrasa as mentioned above, there are several Islamic education institutions (madrasas) in South Lampung that it turns out that it can be considered superior and able to compete with other advanced school institutions - even some of the madrassas are much in demand by the public even though they are private, namely MTs Mathla'ul Anwar Cintamulya, MTs. Hidayatul Mubtadii Jati Agung and MTs. Al Ishlah Sukadamai Natar. Research in three madrasa institutions, this study produced several findings, namely, that first, Educator resource development is based on self-evaluation and needs analysis, program preparation, program implementation; Conduct implementation evaluation; Achievement target; and Orientation of resource development Educators for madrasas. Second, the Educator HR development strategy starts from the "buy" (recruitment) and "make" (coaching / development) process. Third, the form of activities in the context of educating / developing HR Educators is carried out correctly and systematically according to quality standards. Likewise with the development of educational resources (employees) carried out by: planning, training and development, assessment of the percentage of work, employee reward / career planning. The HR development strategy of employees is almost the same as Educators, which starts from the process of "buy" (recruitment) and "make" (coaching / development), which is then carried out correctly and systematically in accordance with quality standards. can be achieved if HR (Educators and Education staff) are optimized through reliable management.